Ambivalences of the Creative Class: Space, reflexivity and the Restructuring of the German Advertising Industry - Joachim Thiel (European Regional Science Association (ERSA), 2004)
One of the most remarkable and successful regional science publications of the last years is certainly Richard Florida's "The Rise of the Creative Class". Based on the key idea that today's economy is increasingly "powered by human creativity" Florida holds that the presence of a non-conformist creative workforce is the crucial factor for the future competitiveness and development of cities and regions. This in turn will substantially change the subject of local economic policy in that it has to be increasingly directed towards the living conditions of this workforce. The suggested paper, despite acknowledging the vital importance of an individualistic – or 'reflexive' – labour force for the (not only) spatial organisation of the future economy, will be strongly critical with Florida's arguments, maintaining that he starts from a too self-evident and monocausal understanding of the relation between creativity/individualism and economic success. Basically it is held that the way from non-conformism to business is full of ambivalences, uncertainties, frictions etc. which have to be dealt with. The spatial dimension of the future economy is based precisely on and shaped by these 'refractions', respectively by the ways to handle them. The argument will be underpinned by highlighting the evidence of an in-depth study of the spatial structure and spatial change of the German advertising industry.
Keywords: 330